Modern Concept of the Financial Strategy of Transport Industry - V. Naydenova, M.; N. Bontsevich, N.; K. Sidelnikova, V. (International Journal of Engineering and Technology, 2018)
The paper states theoretical and methodological issues of financial strategyâ€™s formation of the enterprise under modern conditions of economic development. The key problems of the river ports development are determined. Among them - shortage of service equipment, logistic disparity of transport river networks, obsolete vessels. Ways of improving the financial condition of water transport and ports in Russia are suggested.The article specifies that the strategic management of the company's finances can rule over cash flows, capital and investments effectively. The starting point for formation of financial strategy of water transport enterprises should be diagnostics of financial activity and first of all, diagnostics of financial maintenance of the enterprise. A new methodical approach to the formation of the cash flow management strategy of water transport enterprises is proposed. It includes two main stages: a stage of a strategic analysis of the company's cash flows with use of organizational and information model and aanalysis of diagnostics of financial security of water transport enterprises. It is proved that financial strategy is the guiding vector of management of the enterprise and its industrial and economic activity in a modern, dynamic and competitive market environment.Â Â